A large-scale experiment on New Year’s resolutions: Approach-oriented goals are more successful than avoidance-oriented goals - Oscarsson, Martin; Carlbring, Per; Andersson, Gerhard; Rozental, Alexander (PLOS ONE, 2020)
Despite the popularity of New Year’s resolutions, current knowledge about them is limited. We investigated what resolutions people make when they are free to formulate them, whether different resolutions reach differing success rates, and whether it is possible to increase the likelihood of a resolution’s success by administering information and exercises on effective goal setting. Participants (N = 1066) from the general public were randomized into three groups: active control, some support, and extended support. The most popular resolutions regarded physical health, weight loss, and eating habits. At a one-year follow-up, 55% of responders considered themselves successful in sustaining their resolutions. Participants with approach-oriented goals were significantly more successful than those with avoidance-oriented goals (58.9% vs. 47.1%). The group that received some support was exclusively and significantly more successful compared to the other two. This study reveals that New Year’s resolutions can have lasting effects, even at a one-year follow-up.